Hierarchical assembly of cell–matrix adhesion complexes. (1st June 2004) - Zaidel-Bar, R.; Cohen, M.; Addadi, L.; Geiger, B.
Abstract : The adhesion of cells to the extracellular matrix is a dynamic process, mediated by a series of cell-surface and matrix-associated molecules that interact with each other in a spatially and temporally regulated manner. These interactions play a major role in tissue formation, cellular migration and the induction of adhesion-mediated transmembrane signals. In this paper, we show that the formation of matrix adhesions is a hierarchical process, consisting of several sequential molecular events. One of the earliest steps in surface recognition is mediated, in some cells, by a 1 μm-thick cell-surface hyaluronan coat, which precedes the establishment of stable, cytoskeleton-associated adhesions. The earliest forms of these integrin-mediated contacts are dot-shaped FXs (focal complexes), which are formed under the protrusive lamellipodium of migrating cells. These adhesions recruit, sequentially, different anchor proteins that are involved in binding the actin cytoskeleton to the membrane. Conspicuous in its absence from FXs is zyxin, which is recruited to these sites only on retraction of the leading edge and the transformation of the FXs into a focal adhesion. Continuing application of force to focal adhesions results in the formation of fibrillar adhesions and reorganization of the extracellular matrix. The formation of these adhesions depends on actomyosin contractility and matrix pliability.